Peta Jalan Pendidikan Pariwisata di Indonesia (Konsep, Permasalahan dan Solusi) - Kartika, Titing; Yusuf, Syamsu; Hurriyati, Ratih; Hendrayati, Heny (Jurnal Ilmiah Pariwisata; Vol 26 No 3 (2021): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v26i3.1517, 2021)
Tourism in Indonesia is a new field of science in the academic field. After the official recognition of tourism as a science in 2008, there was a significant development of tourism education in Indonesia at both the high school and university levels. However, in its implementation there are still some obstacles in the implementation of this education, both in terms of human resources (HR), teaching facilities, curriculum, as well as the absorption of graduates in related fields as well as synchronization with industry. The methodology used in this research is descriptive qualitative. Data processing is based on literature and document studies regarding the development of tourism education nationally and globally. Other data collection was also carried out through interviews with tourism education providers. The results showed that solving the existing problems required efforts and commitment from across sectors such as government, industry, academia, and society. Thus the current road map for tourism education is not only seen as a science but can also make a real contribution, namely improving the welfare of the community . Keywords : Tourism Education, Community Welfare, Road Maps, Tourism, Education